Effects of Khat extract and other staining media on color change of composite resins subjected to various polishing methods - Al-Anesi, Waled A.; Madfa, Ahmed A.; Dubais, Mohammed A.; Albahari, Aulfat A. (Herbert Publications PVT LTD, 2019)
Objective: To assess the influence of Khat extract and other staining media on color changes in composite resins subjected to various polishing methods. Methods: 84 disk-shaped specimens (8 mm in diameter and 2 mm thick) were prepared for each composite resin type [nanohybrid (Filtek Z250 XT), nanofilled (Filtek Z350 XT), and microhybrid zirconia/silica (Valux Plus)], for a total of 252 specimens. Each composite group was divided into three subgroups according to polishing methods (n=28): control (no finishing and polishing), polishing Praxis disks, and polishing felt disks. After finishing and polishing, seven specimens from each group were immersed in Khat extract, tea, Pepsi, and distilled water for 7 days. Color parameters were measured before immersion and after the allocated time of immersion. Three-way analyses of variance followed by a one-way ANOVA and Tukeys test were used for the statistical analysis. Results: A significant interaction between the resin composites, polishing methods, and staining solutions were found (p<0.05). The polishing effect on the resin composite color stability was not statistically significant (p>0.05). Of the staining solutions, Khat extract induced the highest level of discoloration. Khat extract and tea revealed significantly more color changes than Pepsi and distilled water (p<0.05). Of the composite resins, the Valux Plus showed the lowest ?E* value, whereas the Filtek Z250 showed the highest (p<0.05). Conclusions: Khat extract showed the highest effects on the color stability of different types of composite resins. Only Khat extract and tea produced clinically perceptible color changes (?E>3.3).